2019
DOI: 10.6065/apem.2019.24.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of linear growth

Abstract: Linear growth occurs at the growth plate. Therefore, genetic defects that interfere with the normal function of the growth plate can cause linear growth disorders. Many genetic causes of growth disorders have already been identified in humans. However, recent genome-wide approaches have broadened our knowledge of the mechanisms of linear growth, not only providing novel monogenic causes of growth disorders but also revealing single nucleotide polymorphisms in genes that affect height in the general population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 111 publications
0
20
0
1
Order By: Relevance
“…We presented IGF-I and IGFBP-3 as growth markers. IGF-1 receptor (IGF-IR) dysfunctions and a reduced number of IGF-IR via gene mutations could lead to IGF-I insensitivity [ 37 ]. Single nucleotide polymorphisms in the IGFBP-3-coding region are associated with height variation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We presented IGF-I and IGFBP-3 as growth markers. IGF-1 receptor (IGF-IR) dysfunctions and a reduced number of IGF-IR via gene mutations could lead to IGF-I insensitivity [ 37 ]. Single nucleotide polymorphisms in the IGFBP-3-coding region are associated with height variation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 receptor (IGF-IR) dysfunctions and a reduced number of IGF-IR via gene mutations could lead to IGF-I insensitivity [ 37 ]. Single nucleotide polymorphisms in the IGFBP-3-coding region are associated with height variation [ 37 ]. Especially, the A allele in the IGFBP-3 promoter region reportedly causes an increase in IGFBP-3 expression, which reflects the growth rate in rhGH therapy in prepubertal children with GHD [ 38 ] and Turner syndrome [ 39 ], but not ISS [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, from genome-wide association study (GWAS) to next-generation sequencing (NGS), the rapid progress of molecular technologies has helped us identify novel genetic causes of SS or single nucleotide polymorphisms (SNPs) of various genes [3]. Yang et al reported that the contribution of common SNPs to the height phenotype is 40% based on GWAS [4].…”
mentioning
confidence: 99%
“…Adanya mutasi pada gen tertentu seperti mutasi pada gen ACAN, FBN1, COL9A2, IGF1R dapat menimbulkan manifestasi klinis perawakan pendek pada bayi hingga remaja. 1,5,6 Remaja merupakan masa transisi antara anak menjadi dewasa. Pada masa ini terjadi pacu tumbuh berat badan dan tinggi badan.…”
unclassified